Experimental Study on the Tribological and Mechanical Properties of Aluminium Bonded with Alumina Ceramic - Jayaprakash, V.; Anish, M.; Senthilkumar, J.; Aakaash, S. R.; Manikandan, K.; Sivabalan, A. King (Current Approaches in Engineering Research and Technology Vol. 8, 2024)
The present study highlights about Tribological and Mechanical Properties of Aluminium Bonded with Alumina Ceramic. Aluminium is a malleable and lustrous substance that is classified as a member of the boron group on the periodic table. Aluminium and its alloys possess a low weight and can provide solutions for optimizing the ratio of strength to weight in cars. However, they are unsuitable for applications that need great resistance to wear. Aluminium alloy is mixed with highly wear-resistant alumina ceramic to enhance its suitability for high-wear applications, such as brakes. Aluminium can withstand corrosion as a result of passivation. Alumina ceramic, a non-metallic material, has excellent resistance to wear. Aluminium may undergo ceramic coating by many methods such as adhesives, brazing, and thermal plasma spraying. Aluminium may be bonded with alumina ceramic using an epoxy resin, which is often used for joining both metals and non-metals. After applying epoxy resin to cover the Aluminium with ceramic, the material was subjected to tribological testing and EDX analysis to conduct research. The material may attain similar mechanical and tribological characteristics.